2015
DOI: 10.1159/000441094
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Signal in Carotid Plaque on Routine 3D-TOF-MRA Is a Risk Factor of Ischemic Stroke

Abstract: Background: Carotid atherosclerotic disease is recognized as an important risk factor for brain ischemic events. However, high-grade stenosis does not always cause ischemic strokes, whereas moderate-grade stenosis may often cause ischemic strokes. It has been reported that there is an association between carotid intraplaque hemorrhage (IPH) and new cerebral ischemic events. The purpose of this study was to elucidate the relationship between high-intensity signals (HIS) on maximum intensity projection (MIP) ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…Moreover, TEE has only limited capabilities in evaluation of the internal structure of plaques, which is relevant for differentiating between stable and potentially vulnerable plaques [18,19]. In this context, MRI [20] and CT imaging [21] or dedicated ultrasound techniques [22,23] may provide additional information; however, those techniques are mostly designed for carotid plaque imaging and not suitable for the aorta. Furthermore, it is beyond the boundaries of this study to establish a causal link between complex plaques in the proximal DAo and stroke, because no control group was included in our study and patients were not followed up prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TEE has only limited capabilities in evaluation of the internal structure of plaques, which is relevant for differentiating between stable and potentially vulnerable plaques [18,19]. In this context, MRI [20] and CT imaging [21] or dedicated ultrasound techniques [22,23] may provide additional information; however, those techniques are mostly designed for carotid plaque imaging and not suitable for the aorta. Furthermore, it is beyond the boundaries of this study to establish a causal link between complex plaques in the proximal DAo and stroke, because no control group was included in our study and patients were not followed up prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients with a score of 0 or 1 had ischemic events, whereas all 3 patients with a score of 7 had ischemic events. When the USR score was classified as low [0, 1], medium [2,3], high [4,5] and very high [6,7] categories, a linear increase in ischemic event risk was observed (P<0.001 for trend; Table 4; Figure 3B). The ischemic event risk was 0% (0/9…”
Section: Usr Score Scalementioning
confidence: 99%
“…Currently, guidelines for prevention on stroke in patients with carotid atherosclerosis are based on quantification of carotid stenosis degree (3,4). However, a growing amount of evidence has shown that vulnerable carotid plaques play an important role in the occurrence of stroke, independent of the severity of carotid stenosis (5,6). This paradigm shift of assessment of the occurrence of ischemic events provides a new strategy for primary and secondary stroke prevention (7).…”
Section: Introductionmentioning
confidence: 99%
“…These two groups of plaques in typical, routinely performed imaging studies are difficult to distinguish. Currently, there are numerous novel imaging techniques that can detect potentially unstable plaques: magnetic resonance imaging, high-resolution computed tomography, positron emission tomography and contrast-enhanced ultrasound (7)(8)(9)(10)(11). Processes indicating plaque activity (molecular imaging) such as: glucose absorption, protein degradation, exposure of adhesive molecules or content of markers for apoptosis are tested for use in the diagnosis of plaques at risk of destabilization (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%